Soft Tissue Reconstruction and Facial Reanimation With Bilateral Latissimus Dorsi Flaps After Extensive Resection of Head and Neck Arteriovenous Malformation: A Case Report. Issue 1 (July 2019) - Wong, Manzhi; Ozaki, Mine; Kurita, Masakazu; Ihara, Aki; Iwashina, Yuki; Takushima, Akihiko
Abstract : Abstract: We report a rare case of a 37-year-old man who presented with a huge arteriovenous malformation in the head and neck region. After resection, the 30 × 25 cm defect was reconstructed with a preexpanded musculocutaneous latissimus dorsi flap. The facial nerve had to be sacrificed during the resection, and smile reanimation was restored in a second operation with the contralateral latissimus muscle flap. A 15-cm length of thoracodorsal nerve was dissected and was anastomosed to the contralateral zygomatic branch in a single stage. He recovered well without any significant complications. At 6 years follow-up, there was no further growth of the arteriovenous malformation, and he had a spontaneous smile.